(untitled) (Sebha University Conference Proceedings, 2024)
Different numerical models have been discussed in recent years to analyze the damage evolution in concrete structures. In this paper, a gradient-enhanced damage model formulation, which is applied to single edge-notched and L-shaped specimens, is explained. A new formulation of the finite element equations is derived, with attention to C0-continuity requirements. This paper focuses on the derivation of the governing equations as well as the implementation of the model with different mesh discretization and discuss the results of the two examples. The difference between non-local damage mechanics and gradient enhanced damage model is also discussed. The exponential softening evolution law is used to define the damage variable and Mazars model of local equivalent strain is applied to simulate the behavior of the problems.